2021
DOI: 10.1021/acs.organomet.0c00765
|View full text |Cite
|
Sign up to set email alerts
|

[Co(NHC)(CO)3]: Isolation and Reactivity Study of a Model 17-Electron Species in the Oxo Process

Abstract: Metrics & MoreArticle Recommendations * sı Supporting InformationABSTRACT: [Co(L)(CO) 3 ] 2 (L = CO or PR 3 ) catalyzed hydroformylation of olefins is among the most successful homogeneous organometallic catalysis. The bimetallic [Co(L)(CO) 3 ] 2 complex exists in equilibrium with its mononuclear 17electron [Co(L)(CO) 3 ] metalloradical. However, isolation of the mononuclear metalloradical is unknown, and hence the role of this species in the catalytic cycle is difficult to study. Herein, we report the isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Complex 5 can be viewed as an analog of (IPr)­Co 2 (CO) 5 and has been fully characterized by various spectroscopic methods. Its molecular structure (Figure S5) is similar to [(6-Mes) 2 Co 2 (CO) 2 (μ-CO) 2 ] (6-Mes = 1,3-dimesityl-1,4,5,6-tetrahydro-pyrimidine-3-ylidene) reported recently …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Complex 5 can be viewed as an analog of (IPr)­Co 2 (CO) 5 and has been fully characterized by various spectroscopic methods. Its molecular structure (Figure S5) is similar to [(6-Mes) 2 Co 2 (CO) 2 (μ-CO) 2 ] (6-Mes = 1,3-dimesityl-1,4,5,6-tetrahydro-pyrimidine-3-ylidene) reported recently …”
Section: Resultssupporting
confidence: 75%
“…Its molecular structure (Figure S5) is similar to [(6-Mes) 2 Co 2 (CO) 2 (μ-CO) 2 ] (6-Mes = 1,3dimesityl-1,4,5,6-tetrahydro-pyrimidine-3-ylidene) reported recently. 47 Testing the catalytic performance of 1−5 in the catalytic reactions of PhCCH with HSiEt 3 then revealed the higher catalytic activity of the mono(NHC)-dicobalt bridging alkyne complex 2 over the other complexes. Monitoring the kinetic profile of the reaction at 60 °C with 1 as catalyst revealed that the reaction involves an apparent induction period (ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4d). The molecular weight (449.17 g mol À1 ), tetrahedral geometry, and charge neutrality of 4 make this molecule the closest structural analog to the tetrahedral 56 and neutral [Co(SIMes)(CO) 3 ] radical (449.41 g mol À1 ) with practically identical molecular weights. 2D DOSY NMR spectra recorded at 24 C showed complete sets of signals from 2-Mes and 4 (Fig.…”
Section: Characterization Of the Paramagnetic Species 2-mes *mentioning
confidence: 99%
“…71 The ligand steric effect is a reliable way to control metal-metal bond strength. 13,56,[72][73][74] In contrast, the ligand electronic effect on metal-metal bond strength is not fully understood 23,68,75 partly due to the lack of an appropriate system to study ligand steric and electronic effects separately. 23 .…”
Section: Elucidation Of Ligand Steric and Electronic Effects On Co-co...mentioning
confidence: 99%
“…Remarkably, the case for six-membered-ring NHCs is reversed. The saturated variants have dominated the literature and conjugated examples based on a perimidine scaffold are rare (Figure A). To date, the complexes that have been characterized are restricted to group 8–10 transition metals with d electron counts of 6 or 8. (Figure B).…”
Section: Introductionmentioning
confidence: 99%